2020
DOI: 10.1128/msphere.00202-20
|View full text |Cite
|
Sign up to set email alerts
|

The mRNA Cap 2′- O -Methyltransferase CMTR1 Regulates the Expression of Certain Interferon-Stimulated Genes

Abstract: Type I interferons (IFN) initiate an antiviral state through a signal transduction cascade that leads to the induction of hundreds of IFN-stimulated genes (ISGs) to restrict viral infection. Recently, RNA modifications on both host and viral RNAs have been described as regulators of infection. However, the impact of host mRNA cap modifications on the IFN response and how this regulates viral infection are unknown. Here, we reveal that CMTR1, an ISG that catalyzes 2′-O-methylation of the first transcribed nucle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
36
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 54 publications
9
36
1
Order By: Relevance
“…Although studies have documented non-canonical activation or delayed stimulation of subsets of ISGs during viral infection, the molecular pathways that control these subsets of ISGs are not well understood ( Pulit-Penaloza et al, 2012 ; Rose et al, 2010 ). However, transcriptional regulators of subsets of ISGs have been identified ( Froggatt et al, 2019 ; Perwitasari et al, 2011 ; Seifert et al, 2019 ), and the mRNA Cap1 methyltransferase CMTR1 can regulate the expression of certain ISGs ( Williams et al, 2020 ). These studies demonstrate that the complexity of ISG regulation extends beyond transcriptional induction.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have documented non-canonical activation or delayed stimulation of subsets of ISGs during viral infection, the molecular pathways that control these subsets of ISGs are not well understood ( Pulit-Penaloza et al, 2012 ; Rose et al, 2010 ). However, transcriptional regulators of subsets of ISGs have been identified ( Froggatt et al, 2019 ; Perwitasari et al, 2011 ; Seifert et al, 2019 ), and the mRNA Cap1 methyltransferase CMTR1 can regulate the expression of certain ISGs ( Williams et al, 2020 ). These studies demonstrate that the complexity of ISG regulation extends beyond transcriptional induction.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, a subset of eukaryotic RNAs lead with the cap 0 structure [113,114]. Strikingly, in one study, all of the detectable cap 0 modifications found in vertebrate mRNA contained m6A as the first transcribed base [113].…”
Section: Rna Recognition Predisposes Fatementioning
confidence: 84%
“…As mentioned, a subset of eukaryotic RNAs lead with the cap 0 structure [113,114]. Strikingly, in one study, all of the detectable cap 0 modifications found in vertebrate mRNA contained m6A as the first transcribed base [113]. A cap 1 moiety with m6A as the first transcribed base is distinct from its internal counterpart and thus has its own designation: 2 -O-dimethyladenosine (m6Am, Figure 4a) [123].…”
Section: Rna Recognition Predisposes Fatementioning
confidence: 94%
See 1 more Smart Citation
“…Several innate immune mobilized antiviral zinc finger protein orthologs are represented in this module, including PARP12 , ZC3HAVIL , TUT4 , and three orthologs of ZNFX1 , one of which is the hub transcript [ 249 , 252 , 292 , 293 ]. Other transcripts are orthologs of interferon-stimulated genes (ISG) that stimulate or facilitate the expression of other ISG, including ZNFX1 , MRE11 , DTX3L , CMTR1 , and IRF1 [ 222 , 226 , 229 , 244 , 248 ]. Among these ISG orthologs are viral dsRNA sensors ZNFX1 and DDX58 / RIG1 [ 222 , 285 ].…”
Section: Discussionmentioning
confidence: 99%